Pemberdayaan Usaha Ekonomi Produktif Bagi Masyarakat Miskin Di kecamatan Ratu Agung Kota Bengkulu - Marjoyo, Marjoyo; Firmansyah, Firmansyah; Sunarti , Elmi (Universitas Dehasen Bengkulu, 2020)
The empowerment of productive economic enterprises for the poor in Kecamatan Ratu Agung, Bengkulu City, is the main focus of efforts to improve social and economic welfare in the region. This study aims to analyze the effectiveness of the economic empowerment program as well as the factors that influence its success. The research method used combines quantitative and qualitative approaches, collecting data through structured surveys and in-depth interviews with local stakeholders. The results show that the majority of poor communities in Kecamatan Ratu Agung have the potential to engage in productive economic enterprises, but there are constraints such as limited capital, market access, and skills that need to be overcome. Other factors affecting the effectiveness of economic empowerment include a lack of support from the local government, complex regulations, and cumbersome bureaucracy. The discussion underscores the need for comprehensive and integrated economic empowerment programs, involving collaboration between local governments, non-governmental organizations, the private sector, and academia. Special attention to the role of women in economic empowerment and regular monitoring and evaluation of implemented programs are also needed. In conclusion, empowering productive economic enterprises for the poor in Kecamatan Ratu Agung, Bengkulu City, requires a holistic and integrated approach to overcome the obstacles faced. Thus, it is expected to improve welfare and reduce poverty levels in the area.